Contrast‐enhanced ultrasound for quantification of tissue perfusion in humans. (17th September 2019) - Emanuel, Anna L.; Meijer, Rick I.; van Poelgeest, Erik; Spoor, Pien; Serné, Erik H.; Eringa, Etto C.
Abstract: Contrast‐enhanced ultrasound is an imaging technique that can be used to quantify microvascular blood volume and blood flow of vital organs in humans. It relies on the use of microbubble contrast agents and ultrasound‐based imaging of microbubbles. Over the past decades, both ultrasound contrast agents and experimental techniques to image them have rapidly improved, as did experience among investigators and clinicians. However, these improvements have not yet resulted in uniform guidelines for CEUS when it comes to quantification of tissue perfusion in humans, preventing its uniform and widespread use in research settings. The objective of this review is to provide a methodological overview of CEUS and its development, the influences of hardware and software settings, type and dosage of ultrasound contrast agent, and method of analysis on CEUS‐derived perfusion data. Furthermore, we will discuss organ‐specific imaging challenges, advantages, and limitations of CEUS.